2006
DOI: 10.1080/00958970600731513
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of transition metal-vitamin B13 complexes mixed with a co-vitamin

Abstract: The synthesis and structural characterization of mixed vitamin-metal complexes are reported. A complex bearing two vitamins (B3 and B13) on the same metal centre, nicotinamide(orotato)nickel(II) pentahydrate, has been prepared and characterised by single-crystal X-ray diffraction methods. A complex of Cr(III) with vitamins C and B13, bis(ascorbato)orotatochromium(III) dihydrate, has been isolated and its nature investigated by means IR, 13 C NMR, API-ES and thermogravimetric measurements. Theoretical calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…High intensity peak was detected at 311 nm for CuII complex that attributed to the metal -> ligand charge transfer band. The results were agreeable to literature [14][15][16][17][18].…”
Section: Electronic Spectrasupporting
confidence: 92%
See 1 more Smart Citation
“…High intensity peak was detected at 311 nm for CuII complex that attributed to the metal -> ligand charge transfer band. The results were agreeable to literature [14][15][16][17][18].…”
Section: Electronic Spectrasupporting
confidence: 92%
“…bands of COOgroup was at 244 cm -1 and it was higher than monoanionic carboxylate group (158 cm -1 ), so it could be suggested that the COO-group was coordinated to metal(II) cation as monoanionic-bidentate in this structure [30,31]. The vibration of Cu-N interaction was emerging at the 469 cm-1, while ascribed to the Cu-O bands were observed at the 596 cm-1 [18].…”
Section: Thermal Analysismentioning
confidence: 77%
“…Itself plays an important role in the metabolism of living cells and some of its metal complexes are biologically active as antibacterial or insulin-mimetic agents [35,36]. N,N-diethylnicotinamide is a derivative of nicotinamide (vitamin B) used as exhalation agent in respiratory systems in medicine [37]. The presence of the pyridine ring in numerous naturally abundant compounds, adducts of Dena are also of scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…In this line of research, metal containing vitamins are increasingly becoming important particularly in drug design and nutrition, with the hope of improving and enriching the quality of existing vitamins, thereby serving as a better substitute as chemotherapeutic agents. [5][6][7] In the search for novel metal complexes, that combine high activity with low toxicity, the study of metal complexes has continued to attract attention of some coordination chemists. [8][9][10] This has also provided useful outlets for basic research in coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%